Future Proofing Education Integrating Digital Innovation and Progressive Pedagogy for Optimal Outcome - Mawar, Mawar; Yana, Meli Handayani (Educia Journal, 2024)
This study investigates the impact of integrating digital innovation and innovative pedagogy on educational outcomes in primary and secondary schools. Using a cross-sectional survey design, data were collected from a stratified random sample of 50 schools, focusing on digital tool usage, teaching practices, and academic results. The findings reveal that both digital innovation and innovative pedagogy significantly enhance student achievement, engagement, and teacher satisfaction. Regression and correlation analyses indicate strong positive relationships between these variables, suggesting that schools with higher levels of integration of these practices experience better educational outcomes. Despite the challenges of access and the rapid pace of technological advancement, the study emphasizes the need for equitable access to digital resources and ongoing teacher professional development to maximize the benefits of these educational innovations.